Pŏmjoe wa ŭi chŏnjaeng nappŭn nomdŭl chŏnsŏng sidae - Yun, Chong-bin; Han, Chae-dŏk; Ch'oe, Min-sik; Ha, Chŏng-u; Cho, Chin-ung (2012)
"Corrupt customs officer Ik Hyun and his cohorts are under investigation for taking bribes, and he's being pressured to take the fall. When he comes across a giant stash of heroine, Ik Hyun decides to secretly sell it off through crime boss Hyung Bae, whom it turns out is actually Ik Hyun's relative. With Hyung Bae's yakuza connections and Ik Hyun's networking skills, the two form a very profitable partnership in these roaring times. But when the government cracks down, the partnership begins to derail"--YesAsia website